Dinâmica do ajuste fiscal do Estado do Ceará 2002–2008 - Santos, Fabrízio Gomes (2009)
The contribution of the work is about the impacts of the Program of Fiscal Adjustment (PAF) in the dynamic management of finances of the State of Ceará, demonstrating how the search for a sustainable debt results in a steady state of fiscal stability. Initially it is conducted an overview analysis of the key concepts of public finances, based on the concepts established by the National Treasury Secretariat, to establish a theoretical introduction to the state's fiscal reality. It made a history of fiscal adjustment and the debt crisis of the state entities, to contextualize the problem. To investigate whether the primary outcome versus Real Net follows a trend stationary or not, the study establishes limits on primary deficits that do not affect debt sustainability. Through an econometric model that aims at defining whether there is trend variables in the period 2002.1 to 2008.12, testing whether there is unit root in the series, is the threshold that defines the sustainability of public debt in the long term. Since then it establishes the existence of two regimes, where the first scheme is debt sustainability in the long term, while in regime two, from a primary deficit, there is the government's concern with the sustainability. Finally, it is made a short analysis from the results of fiscal management performance in 2008, showing in practice the development of key economic indicators.